2001
DOI: 10.1021/ac000553s
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence Determination of 2‘,6‘-Difluorophenyl 10-Methylacridan-9-carboxylate

Abstract: Electrochemical oxidation of the acridan 2',6'-difluorophenyl 10-methylacridan-9-carboxylate produces the corresponding acridinium ester, which reacts with hydrogen peroxide forming a dioxetanone intermediate. Decomposition of the dioxetanone generates light at 430 nm when it relaxes to the ground state. The effect of pH and hydrogen peroxide concentration on this ECL reaction and on the stability of the acridan were investigated. At pH 8.0 and a hydrogen peroxide concentration of 10 mM, light emission from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
12
2
Order By: Relevance
“…More detailed studies of the mechanism of oxidation of 10methylacridan in acetonitrile showed a single two-electron irreversible anodic wave and a one-electron cathodic wave at low sweep rates [25]. In the present study, however, the observation of the two-step oxidation, the influence of oxygen and sweep rate and the presence of double bond at carbon 9 and absence of hydrogen atom at this carbon indicate an oxidation mechanism different from that of other acridans previously described [11,28]. It can be concluded that for the oxidation of Compound 1 at low Scheme 1.…”
Section: Ecl In Peroxide Solutionscontrasting
confidence: 74%
See 1 more Smart Citation
“…More detailed studies of the mechanism of oxidation of 10methylacridan in acetonitrile showed a single two-electron irreversible anodic wave and a one-electron cathodic wave at low sweep rates [25]. In the present study, however, the observation of the two-step oxidation, the influence of oxygen and sweep rate and the presence of double bond at carbon 9 and absence of hydrogen atom at this carbon indicate an oxidation mechanism different from that of other acridans previously described [11,28]. It can be concluded that for the oxidation of Compound 1 at low Scheme 1.…”
Section: Ecl In Peroxide Solutionscontrasting
confidence: 74%
“…The oxidation mechanism of some acridan esters to yield acridinium esters in aqueous solutions has been reported as a two-electron oxidation followed by deprotonation [11,28]. More detailed studies of the mechanism of oxidation of 10methylacridan in acetonitrile showed a single two-electron irreversible anodic wave and a one-electron cathodic wave at low sweep rates [25].…”
Section: Ecl In Peroxide Solutionsmentioning
confidence: 99%
“…Recently it was shown that acridans can also be converted to the corresponding acridinium ester by electrochemical oxidation [34]. ECL of the acridan 2 0 ,6 0 -difluorophenyl 10-methylacridan-9-carboxylate (DMC) has been reported previously [35]. In this article the ECL of a related acridan (TMC) is compared with luminol and RuðbpyÞ 2þ 3 :…”
Section: Introductionmentioning
confidence: 86%
“…Cyclic voltammetry was carried out in the same cell, unless otherwise stated, with an Eco Chemie Autolab PGSTAT20 potentiostat (Eco Chemie, Urtecht, Netherlands). Flow injection measurements were carried out in the thin layer flow cell, with an ITO working electrode and an Ag=AgCl counter=reference electrode, using equipment that has been described previously [35]. The PMT voltage was 1000 V except for detection limit measurements when the voltage was 1500 V.…”
Section: Equipmentmentioning
confidence: 99%
“…Many reagents have been studied and shown to be promising [25,26]. For instance, ruthenium trisbipyridine (Ru(bpy) 2þ 3 [2]) and their derivatives have been recognized as effective probes for oxygen [27,28] and biologically important substances [29][30][31][32] as well as the morphology of chemical composites [33].…”
Section: Introductionmentioning
confidence: 99%